Les gardians de Camargue et leurs chevaux, patrimoine archivistique et photographique pour une étude historique - Frédéric Raynaud (In Situ)
The ‘gardians’ of the Camargue and their horses, an archival and photographic record for a historical study. The Camargue horse is closely associated to the work of the ‘gardians’, mounted livestock guards in charge of keeping and driving the herds of bulls and horses raised in liberty in the uncultivated coastal part of the Camargue. Emerging from medieval traditions, this profession is well documented from the sixteenth century on and has been perpetuated up to the beginning of the twentieth century. The specific characteristic of bull breeding in the Camargue led to the use of young bulls to which the horse, an indispensable actor, modestly leaves pride of place.